Implementasi Pendidikan Karakter Melalui Kultur Sekolah di MTsN Bondowoso II - Firdausih (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research aimed to describe various strategies taken by the school in implementing character education through school culture at MTsN Bondowoso II. This research is a descriptive re- search study using a qualitative approach. This research was conducted at MTsN Bondowoso II, with the subjects consisting of the students and teachers. This study uses a qualitative approach, with descriptive analysis methods. Data collection is done by using quasi observation techniques, participation, interview and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion. Checking the validity of the findings is done by means of peer discussion and triangulation techniques that use source triangulation and methods/techniques. The research results showed that school culture was an important aspect needing close attention in the process of internali- zing character values at school. A number of strategies in implementing character education were, amongothers, routine activities, spontaneous activities, role-modeling, teaching, and strengthening the school environment. The efforts of implementing character education were inseparable from the role modeling of the school principal, teachers, administrative staff, and students who sinergized each other in creating a positive scholl culture. Keywords: implementation of character education; school culture.